Neoadjuvant immune checkpoint inhibition improves protection against hepatic melanoma metastasis - Wohlfeil, Sebastian A.; Weller, Céline; Dietsch, Bianca; Agardy, Dennis; Boschert, Tamara; Vormehr, Sheila Ann; Dormann, Christof; Straub, Niklas; Häfele, Verena; Platten, Michael; Goerdt, Sergij; Géraud, Cyrill (Cancer letters, 2025)
Background - Liver metastasis of cutaneous melanoma (CM) correlates with a decreased response to immune checkpoint inhibition (ICI). Here, we investigated whether neoadjuvant ICI protects against liver metastasis to prevent the development of therapy resistances. - Methods - A stage II CM was modeled by intracutaneous injections of WT31 or B16F10 luc2 melanoma cells. Combined ICI (anti-PD-1/anti-CTLA-4) was applied in murine models of hepatic melanoma metastasis comparing neoadjuvant or adjuvant regimens. Immune cell composition and responses in the liver and CMs were comparatively analyzed by scRNA-Seq, flow cytometry, immunofluorescence, in situ hybridization and multiplex cytokine assays. - Results - Neoadjuvant ICI resulted in improved protection against liver metastasis in comparison to adjuvant therapy. This superior response was associated with an expansion of T cells in CMs, the peripheral blood and the liver. An increased expression of TH1-associated markers and a downregulation of TH2-associated markers were detected in T cells from CMs and livers of mice by scRNA-Seq and immunofluorescence after neoadjuvant ICI. Analysis of hepatic cytokines also revealed lower levels of TH2-associated IL-4 and of IL-15. - Conclusion - Our data demonstrate that neoadjuvant ICI provides superior protection against hepatic melanoma metastasis with a shift towards an anti-tumor TH1 immune response. Therefore, neoadjuvant ICI is a promising therapeutic option for CM to prevent the development of organ-specific therapy resistance mechanisms.